2016
DOI: 10.1097/md.0000000000002747
|View full text |Cite
|
Sign up to set email alerts
|

Whole Grain Intake Reduces Pancreatic Cancer Risk

Abstract: Mounting evidence from epidemiology studies suggests that whole grain intake may reduce pancreatic cancer risk, but convincing evidence is scarce. We conducted a meta-analysis to assess the association between whole grain intake and pancreatic cancer risk.Relevant observational studies were identified by searching PubMed, Embase, Scopus, and Cochrane library databases for the period from January 1980 to July 2015, with no restrictions. We calculated the summary odds ratios (ORs) for pancreatic cancer using ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…Bex is one of the ingredients in cereal and the anti-cancer effect of peptides from cereal has previously been demonstrated (33). Furthermore, meta-analyses indicated that cereal reduces cancer risk (34,35). Thus, the present study provides evidence that dietary components are beneficial for cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 54%
“…Bex is one of the ingredients in cereal and the anti-cancer effect of peptides from cereal has previously been demonstrated (33). Furthermore, meta-analyses indicated that cereal reduces cancer risk (34,35). Thus, the present study provides evidence that dietary components are beneficial for cancer prevention and treatment.…”
Section: Discussionmentioning
confidence: 54%
“…15 Compared with populations with the lowest intakes of dietary whole grains, the populations with the highest intakes observed significant reductions in the incidence of colorectal cancer by 21%, pancreatic cancer by 24% to 30%, and gastric cancer by 43%. 19,21,22 There was no significant change in the RR of developing prostate cancer between these 2 populations. 23 However, although 2 meta-analyses reported significant reductions in the incidence of developing colorectal cancer, 1 meta-analysis identified a nonsignificant reduction in RR of only 6%.…”
Section: Citation Matrix For Meta-analyses On Type 2 Diabetes Incidmentioning
confidence: 84%
“…Higher whole grain consumption is widely accepted to be able to reduce colorectal cancer risk (Aune et al, 2011;Kyro et al, 2014;Larsson, Giovannucci, Bergkvist, & Wolk, 2005;Schatzkin et al, 2007). Moreover, another meta-analysis of observational studies suggested that whole grain intake was associated with a decreased risk of pancreatic cancer (Lei et al, 2016). However, there was no association between whole grain consumption and prostate cancer (Egeberg et al, 2011), breast cancer among postmenopausal women (Egeberg et al, 2009), and endometrial cancer (Kasum, Nicodemus, Harnack, Jacobs, & Folsom, 2001).…”
Section: Discussionmentioning
confidence: 99%